Akibat Hukum bagi Anak yang Lahir dari Perkawinan Keris (Studi Kasus di Desa Baturiti, Banjar Tengah) - Ni Kadek Febriana; I Nyoman Gede Sugiartha; I Nyoman Subamia (Fakultas Hukum, Universitas Warmadewa, 2022)
Marriage is generally carried out between a woman and a man, but in fact there is a marriage procession carried out between a woman and a keris which is often called a keris marriage. Thus, this has legal consequences for the child who is born. So, the purpose of this study is to discuss the factors that influence the bride to choose a keris marriage and the legal consequences for children born from a keris marriage. This research method uses empirical research methods using a sociological approach to law by examining the issues raised based on facts supported by a juridical approach in relation to the problems discussed. The primary data sources are: Data in the form of observations and interviews with residents in the Baturiti Traditional Village. While secondary data sources are: Data obtained by conducting library research available from reviewing legal literature, official documents, laws and other data related to theoretical problems as a legal basis. Research results include: the factor of the bride choosing a keris marriage in Baturiti Village, Central Banjar because the woman has the status of a sentana rajeg, the man is reluctant to take responsibility, the woman is already pregnant, avoiding the birth of a bebinjat child. The legal consequences for children born from kris marriages by KK registration and birth certificates have a civil relationship with their mother only, by inheritance the child has the right if he has no more relatives and at the decision of his mother. If the child is adopted by his grandfather (squeezing) then the status of the child becomes the child of his grandfather